Situasi, Kendala Dan Strategi Pengembangan Ekonomi Kreatif Kuliner Di Kabupaten Fakfak Provinsi Papua Barat - Els Tieneke Rieke Katmo; Agus Sumule; Ardha Puspitasari; Diana Irbayanti; Indra Irianti; Maria I. Arim (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
Culinary is a potential creative economic sector in Fakfak in enhancing slow economic growth. In comparison to other creative economic sector, creative economic mapping in Fakfak indicated that culinary has highest scores. SWOT analysis that was applied to assess criterias of indicators from three dimentions which are sectors, process and actors indicated that human resources is the main strength but also weaknesses in culinary as well as raw material as resources that naturally provided. National Government policy regarding creative economic is strength in develops creatice economic in Fakfak. Yet, sustainability of culinary as potential creative economic sector depends on sustainability of natural resources and agriculture product. Threfore, increasing production process while improving the use of technology and infrastructure in creation is needed. This followed by market expansion.